FORMULATION AND EVALUATION OF IBUPROFEN CONTROLLED RELEASE MATRIX TABLETS USING ITS SOLID DISPERSION - MANNA, SREEJAN; KOLLABATHULA, JYOSHNA (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the present work was to prepare solid dispersion of ibuprofen with PEG 6000 to increase the aqueous solubility of the drug and to develop the solid dispersed ibuprofen into tablet formulation with the combination of a hydrophilic and hydrophobic polymer to attain controlled release of ibuprofen. Methods: Solid dispersion of ibuprofen was prepared by melting-solvent method by varying the ratio of drug and PEG 6000. The solid dispersed ibuprofen was subjected to tablet formulation by using a hydrophilic swellable polymer-carbopol and hydrophobic non-swellable polymer-ethyl cellulose. The release of the drug from the polymer matrix was studied as the polymer ratio changes. Results: Compatibility between drug and polymers was established from FT-IR study. The saturated solubility was found to increase in the solid dispersed formulation. The swelling index was found within the range of 90±5.43 to 137±6.41. SEM image of swollen tablet confirmed the presence of irregular and porous surface. The cumulative drug release was found to vary within the range of 68.76±3.04 to 95.33±2.34 % after 8 h of dissolution. Conclusion: The combination of solid dispersion and application of hydrophilic and hydrophobic polymers in matrix formation can facilitate better dissolution and absorption profile with greater patient compliance.